Climate and health concerns of Montana's public and environmental health professionals: a cross-sectional study - Lori Byron; Karen L. Akerlof (BMC, 2021)
Abstract Background Rural health professionals stand at the forefront of community response to climate change, but few studies have assessed their perceptions of the threat. Further, no previous study has compared the opinions of environmental to public health professionals or extensively analyzed the factors related to these experts' climate beliefs, risk perceptions, and issue prioritization. Methods In conjunction with the Montana Climate Assessment's 2021 Special Report on Climate Change and Human Health, the 479 members of the Montana Public Health Association and Montana Environmental Health Association were surveyed during September-October 2019, with 39% completing the survey. We summarized descriptive data about their perceptions of local climate-related changes and their beliefs that global warming is happening, is mostly human-caused, is a risk to human health, and that their offices and others should take action. We also evaluated which sociodemographic and risk perception factors related to these climate beliefs, risk perceptions, and workplace issue prioritization. Results Health professionals in Montana, a politically conservative state, demonstrated high levels of awareness that global warming is happening, human-caused, and a threat to human health, well above reported rates of public concern. Eighty-eight percent said that global warming is occurring and 69% that it is mostly anthropogenic. Sixty-nine percent said that their own health was already affected by climate, and 86% said they were already seeing at least one climate change-related event in their communities. Seventy-two percent said that their departments should be preparing to deal with climate change's health effects, but just 30% said that it is currently happening. We found no statistically significant differences between Montana environmental health and public health professionals in regression models predicting climate beliefs, risk perception, and prioritization. As in studies of the public, political ideology and the observation of local climate-related changes were the strongest factors. Conclusions Montana environmental and public health officials said that departmental action was needed on climate change, indicating the readiness of rural health professionals to take action. Further studies of health professionals in rural regions are warranted.